1991
DOI: 10.1111/j.1471-4159.1991.tb08295.x
|View full text |Cite
|
Sign up to set email alerts
|

Agonist‐Dependent Internalization of γ‐Aminobutyric AcidA/Benzodiazepine Receptors in Chick Cortical Neurons

Abstract: An impermeant benzodiazepine receptor ligand was prepared by derivatization of the aminobenzodiazepine 1012-S with 4-sulfophenylisothiocyanate. The resulting N-(4-sulfophenyl)-thiocarbamoyl derivative of 1012-S (SPTC-1012S) was purified by reverse-phase HPLC, and the predicted structure was verified by mass spectrometry. The apparent affinity of SPTC-1012S (IC50 = 9.8 +/- 2.9 nM) for displacement of [3H]flunitrazepam from intact chick cortical neurons was similar to that of 1012-S (IC50 = 4.0 +/- 0.3 nM). Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 11 publications
1
45
0
1
Order By: Relevance
“…Studies in which the organotypic cultures were exposed to either excessive extracellular GABA concentration with GABA uptake blocked or to the high affinity GABAR agonist muscimol also demonstrated that modulation of the surface expression of the ␥2 subunit was not dependent on direct ligand binding of the receptor. Although previous studies have demonstrated a ligand-dependent mechanism for the regulation of the surface expression of GABARs, these studies (Tehrani and Barnes, 1991;Calkin and Barnes, 1994) used longer incubation periods and higher concentrations of GABA than that used in the present study.…”
Section: Subunit-specific Trafficking Of Gabarsmentioning
confidence: 76%
See 1 more Smart Citation
“…Studies in which the organotypic cultures were exposed to either excessive extracellular GABA concentration with GABA uptake blocked or to the high affinity GABAR agonist muscimol also demonstrated that modulation of the surface expression of the ␥2 subunit was not dependent on direct ligand binding of the receptor. Although previous studies have demonstrated a ligand-dependent mechanism for the regulation of the surface expression of GABARs, these studies (Tehrani and Barnes, 1991;Calkin and Barnes, 1994) used longer incubation periods and higher concentrations of GABA than that used in the present study.…”
Section: Subunit-specific Trafficking Of Gabarsmentioning
confidence: 76%
“…Although reduced, this decrease did not reach statistical significance ( p ϭ 0.08, t test). A reduction in the surface expression of a subset of GABARs during SE could occur in response to either a ligand-independent mechanism (Stelzer and Shi, 1994;Chen and Wong, 1995;Lu et al, 2000) or a ligand-dependent mechanism (Tehrani and Barnes, 1991;Calkin and Barnes, 1994). The finding that NMDA was, at a minimum, necessary to induce a reduction in the surface expression of the ␥2 subunit in the organotypic culture is consistent with a ligand-independent mechanism.…”
Section: Changes In the Surface Expression Of Gabars Are Independent mentioning
confidence: 99%
“…Furthermore, we have shown that a peptide corresponding to the AP2 dileucine motif region of the receptor ␤ 2 subunit increases GABA-gated chloride currents in HEK 293 cells expressing recombinant receptors and also in cerebral cortical neurons. The observations that GABA A receptor cell surface expression is rapidly decreased following GABA A receptor stimulation (29), ischemia (30), and exposure of neurons to brain-derived neurotrophic factor (31) underscore the importance of understanding the mechanisms that regulate GABA A receptor endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these changes include internalization of the receptor, a subsensitivity to GABA, an uncoupling of sites at the GABA receptor complex (Wilson & Gallager, 1988;Roca et al, 1989;Tehrani & Barnes, 1991). Other mechanisms that might be involved are alterations in levels of GABA receptor subunit mRNA and receptor phosphorylation (Kang & Miller, 1991;Gyenes et al, 1994;Wu et al, 1994).…”
Section: Discussionmentioning
confidence: 99%